Pengaruh Kelengkapan Pencatatan Form Tindakan terhadap Mutu Rekam Medis di Puskesmas Pakutandang - Maylan Rahmawati; Riki Solihin; Erix Gunawan (Jurnal Health Sains, 2021)
Medical records are very important documents in the medical world because in medical records describe the patient's medical history, actions, treatment and other documents ranging from patient diseases in health facilities to patientspu lang. The specific purpose of this study is to find out the adequacy of filling out the patient identification and authentication action form at the Klinik Gigi Puskesmas Pactndang. The type of research used is qualitative descriptive research that has the aim to identify the completeness of filling out the poly dental action form at pakutandang health center. Under the law medical records must be completed within 24 hours before the end of outpatient services. To avoid incompleteness of the contents of outpatient medical records, an in-depth study of medical record samples is conducted. This research was conducted at Pakundang Health Center using descriptive statistical methods. The object of the study is in the form of actions in March - April 2021. The sample count studied was 15 randomly taken samples from a total of 150 action forms in March - April. According to the results of the study conducted, 14 samples or 94% of medical records examined are incomplete. Lack of completeness is mainly found in the signatures of doctors who treat as many as 10 forms or 67%. From these results it is expected that in the future it can reduce the incompleteness of medical record forms at Pakundang Health Center